Bringing nature home : how you can sustain wildlife with native plants - Tallamy, Douglas W. (Timber Press, 2009)
In Bringing Nature Home, Doug Tallamy encourages the use of native plants in gardening. This book asks and answers questions for modern gardeners inclined to good stewardship. How can we adjust our planting palette to be both beautiful and environmentally useful? How much more does a local oak species contribute to habitat richness then an out-of-ecological-context exotic tree? What do violets and fritillary butterflies, or pawpaws and zebra swallowtails have in common? Where might tomorrow's species come from?